The Effect of Company Size, Leverage, and Profitability on Financial Performance in Food and Beverage Companies Listed on the Indonesian Stock Exchange (BEI) in 2022-2023 - Erika Safitri; Ramadhan Harahap; Hernawaty (Penerbit Jurnal Indonesia, 2025)
The aim of this research is to examine the effect of company size measured by the natural logarithm (Ln) of total assets, leverage (DAR) profitability (ROE) on financial performance (NPM) in food and beverage companies in 2022-2023. The sample selection technique was purposive sampling, the sample consistend of 31 companies. The data analysis technique in this research is descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, hypothesis testing and coefficient of determination testing, by applying software SPSS ver 25. The results of the research show that partially company size has no significant effect on financial performance, while individually (partially) leverage and profitability have a significant effect on financial performance. Simultaneously company size, leverage and profitability have an effect on financial performance.